Preparative Separation, Identification and Characterization of N-Acylated Impurity in Ciprofloxacin Eye Drops Formulations Using 1D and 2D NMR Techniques - Kumar, Bhupinder; Mudhulkar, Raju; Gundekari, Sreedhar; Tiwari, Surbhi; Rao, Dama Venugopala; Prakash, Lakki Reddy; Belly, Ramakrishna Yadav; Kumar, Sandeep (International Journal of Pharmaceutical Investigation, 2026)
Background Packaging, storage and transportation of under varying climatic conditions have the quality concern in the drug products. This study followed the observed unknown impurity of ciprofloxacin eye drop. Materials and Methods The drug product of ciprofloxacin was stored 30ºC±2ºC/65% RH±5% RH for 18 months and was analysed with High-Performance Liquid Chromatography (HPLC). The impurity observed was isolated with preparative HPLC. The isolated impurity was structurally elucidated using 1D and 2D Nuclear Magnetic Resonance (NMR) and High-Resolution Mass Spectrometry (HRMS). Results During stability study of Ciprofloxacin eye drops, the formation of an impurity was observed. Notably, the impurity level reached 0.30% (exceeding the specification limit of 0.20%) in 18 months (30ºC±2ºC/65% RH±5% RH) stability samples of Ciprofloxacin eye drops (3 mg/mL). The Relative Retention Time (RRT) 1.19 impurity was isolated and purified using preparative High-Performance Liquid Chromatography (HPLC) and analyzed using advanced spectroscopic techniques, including LC-HRMS and NMR. Preparative HPLC was employed a Kinetix phenyl-hexyl preparative column (250×20 mm, 5 µm) with a mobile phase consisting of 0.1% Trifluoroacetic Acid (TFA) in water and acetonitrile. Results showed that the impurity was N-acylated derivative of Ciprofloxacin. It was determined that the impurity resulted from a condensation reaction between the drug product and a migrated component, possibly from the ink or varnish used on the label affixed to the Low-Density Polyethylene (LDPE) bottle. The impurity was identified as N-(3-Hydroxypropionyl) Ciprofloxacin. The hypothesis of the formation 3-hydroxypropionic acid via acrylic acid leading to the generation of N-(3-Hydroxypropionyl) Ciprofloxacin (HP-CIP) was confirmed by intentional reaction between them. Conclusion This finding raises concerns regarding the quality and efficacy of other products with similar chemical properties stored in comparable container closure systems.
Keywords: Ciprofloxacin; N-(3-Hydroxypropionyl) Ciprofloxacin; Impurity isolation; High-Resolution Mass Spectrometry (HRMS); Nuclear Magnetic Resonance (NMR).